Analisis Rendahnya Academic Self-Efficacy pada Siswa Kelas XII SMA Negeri 3 Payakumbuh - Utri Raihani; Hidayani Syam; Zuria Gessuri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Academic self-efficacy is a belief based on students' self-confidence in their ability to complete academic assignments, achieve desired academic results, and achieve optimal results. In general, this research aims to identify the low academic self-efficacy of class XII students at SMA Negeri 3 Payakumbuh. This research was carried out in Class XII MIPA 2. Qualitative methodology using descriptive designs or patterns was used in this research. Interviews and observations are the data collection methods used. An interactive model that includes data reduction, data presentation, and drawing conclusions is used in this research. Although low effort, task avoidance, and inability to complete assignments are characteristics of students' low academic self-efficacy, research reveals that internal factors such as lack of enthusiasm, lack of learning motivation, and lack of learning ability, among others, are the factors that actually cause self-efficacy. low student academic self. causes low student academic self-efficacy. External factors include students not listening to instructions from classmates and homeroom teachers, as well as a lack of guidance from homeroom teachers, which can cause students to give up too quickly, cheat, and lose interest in learning. The role of the Guidance and Counseling instructor is to provide individual and group counseling.